Differences between Old and Young Adults’ Ability to Recognize Human Faces Underlie Processing of Horizontal Information - Obermeyer, Sven; Kolling, Thorsten; Schaich, Andreas; Knopf, Monika (Frontiers in Aging Neuroscience, 2012)
Recent psychophysical research supports the notion that horizontal information of a face is primarily important for facial identity processes. Even though this has been demonstrated to be valid for young adults, the concept of horizontal information as primary informative source has not yet been applied to older adults’ ability to correctly identify faces. In the current paper, the role different filtering methods might play in an identity processing task is examined for young and old adults, both taken from student populations. Contrary to most findings in the field of developmental face perception, only a near-significant age effect is apparent in upright and un-manipulated presentation of stimuli, whereas a bigger difference between age groups can be observed for a condition which removes all but horizontal information of a face. It is concluded that a critical feature of human face perception, the preferential processing of horizontal information, is less efficient past the age of sixty and is involved in recognition processes that undergo age-related decline usually found in the literature.